2018
DOI: 10.12669/pjms.341.14071
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of single femoral nerve block in combination with general anesthesia on geriatric patients receiving total knee arthroplasty

Abstract: Objective:To evaluate the clinical effects of single femoral nerve block (sFNB) combined with general anesthesia on geriatric patients receiving unilateral total knee arthroplasty (UTKA).Methods:Sixty geriatric UTKA patients who were treated in The First People's Hospital of Changzhou from January 2015 to August 2015 were randomly divided into an sFNB + laryngeal mask airway (FLA) group, an sFNB + tracheal intubation (FGA) group and a tracheal intubation (GA) group. Their clinical parameters and indices were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Reduction in the pain intensity, judged according to the lower scores on the NPS in comparison with the opioid group, found in the FNB group was in accordance with the results of several other clinical trials. [29][30][31][32][33][34][35][36] Publications on the postoperative efficacy of FICNB are less abundant, but a meta-analysis unequivocally confirms the results of the present study. 37 One of the rare available clinical studies publishing the head-tohead comparison between 3-in-1 FNB and FIC-NB found no difference in the efficacy and safety of these two multi-modal analgesic techniques, 34 corroborating thus the current results.…”
Section: Mp -Morphine Paracetamol Fnb -Femoral Nerve Block Ficnb -Fsupporting
confidence: 81%
“…Reduction in the pain intensity, judged according to the lower scores on the NPS in comparison with the opioid group, found in the FNB group was in accordance with the results of several other clinical trials. [29][30][31][32][33][34][35][36] Publications on the postoperative efficacy of FICNB are less abundant, but a meta-analysis unequivocally confirms the results of the present study. 37 One of the rare available clinical studies publishing the head-tohead comparison between 3-in-1 FNB and FIC-NB found no difference in the efficacy and safety of these two multi-modal analgesic techniques, 34 corroborating thus the current results.…”
Section: Mp -Morphine Paracetamol Fnb -Femoral Nerve Block Ficnb -Fsupporting
confidence: 81%
“…A certain dose of additional intravenous sedatives or general anesthesia is required to obtain the best anesthetic effect, resulting in guarantee of adequate oxygen supply during surgery. A study of total knee arthroplasty demonstrated that femoral nerve block combined with general anesthesia alleviated postoperative pain and exhibited declined 6 h and 24 h VAS scores in resting state after surgery [ 31 ]. In the present study, comparing to general anesthesia group, the combined anesthesia group had much lower VAS score at 6 h, 12 h, and 24 h after surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 More recently, there has been an increase in the emphasis of scientific investigations involving hip surgery, whereas only three studies were published from 2003 to 2013. In the current period, femoral nerve block is described for hip surgery (total hip arthroplasty or hip arthroscopy), 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 femoral fracture, 48 , 49 , 50 knee surgery (total knee arthroplasty, anterior cruciate ligament reconstruction), 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 51 , 52 , 53 , 54 , 55 , 56 , 57 and tibial fracture/osteotomy. 58 , 59 Endovenous laser ablation is also described as an indication for femoral nerve block.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of femoral nerve blocks used ultrasound guidance (22 studies), 23 , 26 , 28 , 29 , 30 , 31 , 32 , 33 , 35 , 36 , 37 , 39 , 42 , 47 , 48 , 49 , 54 , 56 , 57 , 59 , 60 , 61 but 10 studies used nerve stimulation, 22 , 27 , 34 , 40 , 41 , 44 , 45 , 46 , 50 , 52 and eight studies did not report the nerve identification technique or were not clear in their description. 24 , 25 , 38 , 43 , 51 , 53 , 55 , 58 …”
Section: Resultsmentioning
confidence: 99%